Tinea nigra: rare and almost never remembered superficial mycosis - Belda, Walter; Carvalho, Caroline H. (International Journal of Research in Medical Sciences, 2024)
Tinea nigra is a chronic fungal infection of the stratum corneum caused by the fungus Hortaea werneckii, clinically manifested by asymptomatic and hyperchromic macules ranging in color from light brown to black and affecting mainly the palmar and plantar areas. must be differentiated mainly from acral melanoma. It occurs mainly in South America (Brazil, Colombia, Venezuela), Central America and the Caribbean (Panama, Cuba), Asia (India, Japan, Sri Lanka) and the coastal regions of Africa and is uncommon in Europe, correlated with travel and immigration intercontinental. In relation to Brazil in the period 1916-2020, 203 cases were reported. We present a case of palmar tinea nigra in an adult patient with 3 months of evolution, diagnosed through clinical examination, direct mycological examination, Sabouraud agar culture, and dermatoscopy of the lesion was also performed. who fully responded to topical therapy with miconazole.